Digital Marketing Interactions: Moderating the Relationship between Instagram Marketing and Tourist Decision-Making Behaviour - Sayani Chawla; Ritu Sood; Amit Chawla (Recoletos Multidisciplinary Research Journal)
Innovative social media marketing techniques, particularly on Instagram, are being employed to connect with prospective travelers who often check these sites for destination information, reviews, recommendations, photos, videos, and experiences. This research aims to identify how Instagram marketing, comprehensive travel reviews, and consumer engagement influence tourist decision-making. Furthermore, it seeks to examine how digital marketing with practical insights for marketers and professionals in the tourism industry influences tourist behaviour. The findings are based on empirical analysis, with primary data collected using a structured questionnaire through an online survey of 493 respondents from the Delhi-NCR region. The analysis reveals that Instagram marketing positively impacts tourist decision-making. Digital marketing interactions also moderate the relationship between Instagram marketing and tourist behaviour. These findings enrich existing knowledge and offer valuable insights for tourism marketers and professionals.